POLIKULTUR TANAMAN KELAPA SAWIT (Elaeis quineensis Jacq.) DENGAN TANAMAN JELUTUNG (Dyera polyphylla) - Nasamsir Nasamsir; Usman Usman (Universitas Batanghari, 2019)
Oil palm planting can be done between rows of jelutung plants, resulting in optimal growth and productivity of the land. The research will be conducted in Betara and Bram Itam Kanan , Tanjung Jabung Barat, with the condition of peatland will be conducted from Mei to Juny 2019. This study aims to determine the value of land equivalent ratio (LER) in the intercropping of oil palm with jelutung plants. This research used survey method on farmers' land planted monoculture and intercropping with oil palm and jelutung plant. The location of this study was chosen intentionally because at these locations there is a cultivation of intercropping with oil palm and jelutung plants. The observed variables are; planting distance (m), stem height (m), stem circumference (cm), leaf color, age of production (years), productivity of the oil palm and jelutung plants in intercropping (ton), and land productivity. To answer the proposed hypothesis, the data obtained in the field is done statistical analysis with Z test and descriptive method in the form of tabulation. The results showed that the production of oil palm and Jelutung monoculture system cropping were more than polyculture system cropping, but based on the calculation of the value of land equivalent ratio (LER), that value was > 1 (1.4).